2015
DOI: 10.1093/annonc/mdv281
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of EP2006, a filgrastim biosimilar, to the reference: a phase III, randomized, double-blind clinical study in the prevention of severe neutropenia in patients with breast cancer receiving myelosuppressive chemotherapy

Abstract: This randomized, double-blind comparison demonstrates that biosimilar filgrastim (EP2006) and the US-licensed reference filgrastim are similar with no clinically meaningful differences regarding efficacy and safety in prevention of severe neutropenia. Biosimilar filgrastim could represent an important alternative to the reference product, potentially increasing access to filgrastim treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 18 publications
4
76
0
Order By: Relevance
“…For example, in the phase III randomized trial comparing biosimilar filgrastim (EP2006) with the original product (Neupogen ® ; Amgen Inc., Thousand Oaks, CA, USA) in the prevention of severe neutropenia in 218 patients with breast cancer receiving chemotherapy [according to the TAC (docetaxel, doxorubicin and cyclophosphamide) protocol], no significant differences in efficacy and safety were observed (11). There was also no difference between the studied preparations in the duration of severe neutropenia during the first cycle of treatment, which was the primary endpoint of the study (1.2 days for the biosimilar filgrastim and 1.2 days for the original preparation, respectively) (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the phase III randomized trial comparing biosimilar filgrastim (EP2006) with the original product (Neupogen ® ; Amgen Inc., Thousand Oaks, CA, USA) in the prevention of severe neutropenia in 218 patients with breast cancer receiving chemotherapy [according to the TAC (docetaxel, doxorubicin and cyclophosphamide) protocol], no significant differences in efficacy and safety were observed (11). There was also no difference between the studied preparations in the duration of severe neutropenia during the first cycle of treatment, which was the primary endpoint of the study (1.2 days for the biosimilar filgrastim and 1.2 days for the original preparation, respectively) (11).…”
Section: Discussionmentioning
confidence: 99%
“…There was also no difference between the studied preparations in the duration of severe neutropenia during the first cycle of treatment, which was the primary endpoint of the study (1.2 days for the biosimilar filgrastim and 1.2 days for the original preparation, respectively) (11). No differences in other clinically relevant features (including the incidence of FN, the need for hospitalization due to FN, the incidence of infectious complications, depth and time of the ANC nadir and the normalization of ANC) during the first and all subsequent cycles of treatment were observed (11). In a previous non-interventional observational study involving >1,300 patients undergoing chemotherapy (the HEXAFIL study), the clinical usefulness, efficacy and safety of biosimilar filgrastim was evaluated (12).…”
Section: Discussionmentioning
confidence: 99%
“…[8] Two pivotal studies were performed specifically for the US and were performed head-to-head against the USlicensed reference product: one study evaluating pharmacokinetics and pharmacodynamics (Figure 1d) in healthy volunteers and one study evaluating safety and efficacy in breast cancer patients undergoing chemotherapy. [9] The EU-approved comparator product was used in a total of five animal studies comparing pharmacodynamics, toxicity, toxicokinetics, and local tolerance and in five PK/PD studies in healthy subjects. [5,6] Since the absolute neutrophil count (ANC) is a well-established PD marker that drives diagnosis and treatment in patients and donors and which can be sensitively measured in healthy volunteers, the EMA approval was based on establishing PK bioequivalence and PD equivalence across a wide range of doses (1-10 mcg/ kg) using single and multiple s.c. or i.v.…”
Section: Nonclinical and Clinical Studies -Resolving The Residual Uncmentioning
confidence: 99%
“…The additional confirmatory clinical trial in breast cancer patients was designed to investigate the effects of multiple switches to address interchangeability as part of further interactions with the FDA as the standards for interchangeability are still being developed. [9] Based on an extensive analytical bridge established between the biosimilar and both the US-licensed reference and the EU-approved comparator product, data generated across all studies conducted was considered relevant for FDA approval. Post-marketing pharmacovigilance is an important additional measure to provide evidence that a biosimilar is comparable to the reference product in terms of its safety profile.…”
Section: Nonclinical and Clinical Studies -Resolving The Residual Uncmentioning
confidence: 99%
“…Multinational Association of Supportive Care in Cancer (MASCC) highlights the significance of G-CSF administration also when applied chemotherapy regimen is associated with FN risk between 10-20% and patients present certain characteristics that may result in higher susceptibility to FN. Two chemotherapy regimens administered to breast cancer patients, TAC [6] (docetaxel, doxorubicin and cyclofosfamide) and AT [7] (doxorubicin and docetaxel), are associated with high risk of FN. Typically breast cancer patients receive G-CSFs injections after each cycle of chemotherapy, though some studies have shown that exposure to GCSFs is associated with an elevated risk of venous and arterial thrombosis [8] Mechanisms underlying this effect are still under investigation.…”
mentioning
confidence: 99%